Effectiveness of Walking to Reduce High Blood Pressure in Hypertension Patients: Literature Review - Firmansyah, Moh. Wahyu; Hardianti, Sri (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. Hypertension is among the most prevalent chronic non-communicable disorders in society. The causes encompass unhealthy lifestyles, including insufficient physical activity, excessive food intake, and many detrimental habits. Materials and Methods. This paper seeks to evaluate the efficacy of walking in lowering hypertension in individuals with elevated blood pressure. This study employs a literature review methodology utilising the Google Scholar database and the Garuda portal, focusing on publications from 2020 to 2024. Materials and Methods. The research employs a literature review methodology utilising the Google Scholar database and the Garuda portal, focusing on publications from 2020 to 2024. Hasil. Seven articles were identified that fulfilled the requirements based on the analysis results. Conclusion Regular walking for 20-30 minutes has been demonstrated to effectively reduce blood pressure in individuals with hypertension.